Nutritional Composition and Hypocholestrolemic Effect of Canarium Odontophyllum Miq. Fruit in Rabbits - Shakirin, Faridah Hanim (2011)
The main objective of this study was to determine nutrient composition, antioxidant properties of Canarium odontophyllum Miq. (CO) fruit and its effect on selected cardiovascular biomarkers in hypercholesterolemic and normocholesterol rabbits. Proximate composition of CO fruit pulps was determined in this study. For powdered full-fat, the fruit was rich in fat, total dietary fiber (TDF) and carbohydrate. For powdered defatted pulp, the fruit was rich in TDF and carbohydrate. CO fruit was also rich in minerals such as potassium, magnesium and calcium. Pulp and kernel oils were rich in palmitic acid and oleic acid. Total phenolic content (TPC) of samples (fruit parts and oil extracts) were determined using spectrophotometer. The TPC of the oils were in the order of; pulp oil (with skin) > pulp oil (without skin) > kernel oil. Meanwhile, the TPC of the different parts of CO was in order of skin (S) > flesh with skin (SF) > flesh (F) > kernel (K). Antioxidant capacities of the different parts of CO (S, SF, F and K) was measured using three different assay; β-carotene bleaching assay, scavenging activity on DPPH and ferric reducing/antioxidant power (FRAP) assay. The antioxidant activities of fruit extracts were in the order of: S > SF > F > K except for DPPH assay. The lipid lowering effect of CO fruit parts was investigated in hypercholesterolemic rabbits (Study I) and normocholesterol rabbits (Study II). The parameter used in this studies are plasma lipid profile [ Total cholesterol (TC), low density lipoprotein-cholesterol (LDL-C), high density lipoprotein-cholesterol (HDL-C), plasma malondialdehyde (MDA), antioxidant enzymes [glutathione peroxidase (GPx), superoxide dismutase (SOD), catalase (CAT)], total antioxidant status (TAS) and toxicity test [aspartate aminotransferase (AST), alanine aminotransferase (ALT) and gamma-glutamyl transpeptidase (GGT)]. The percentage of lesion of atheroma plaque was determined in this study. In Study I, supplementation of defatted pulp of CO in hypercholesterolemic rabbits showed the greatest lipid lowering effects and increased antioxidant status. The presence of high dietary fiber content and high antioxidant activity in the defatted pulp was the possible factors contributing to the retardation of atherosclerosis and reducing the risk of coronary artery disease (CHD). However, no significant effects of pulp and kernel oils of CO were found in the hypercholesterol study. Thus, the effect of oils of CO was tested in normocholesterol rabbits (Study II). In Study II, supplementation of pulp and kernel oils of CO were found beneficial in reducing the CVD risks. Consumption of pulp oil in rabbits resulted in significant increased of plasma TC and HDL-C levels and lowered plasma LDL-C level. Pulp oil resulted in increased TAS level, erythrocyte GPx and SOD activities, and reduced plasma lipid MDA levels. There were elevation in ALT, AST and GGT activities in pulp oil supplemented group as compared to control. In this study, supplementation of kernel oil of CO was found beneficial in reducing CVD risk factors as it resulted in significant reduction of plasma TC, increased HDL-C, lowered LDL-C and TG. However, the LDL-C to HDL-C ratio was significantly higher in animal fed-kernel oil compared to animal fed normal diet. No toxic effect was found in relation to consumption of the kernel oil. As conclusion, defatted pulp and oil extracted from CO showed protective effect towards the CVD biomarkers. The protective effects could be due to high phenolic content and high antioxidant activity in the fruits.